The Role of Youtube in Building Brand Image Communication in Technology Review Content on the Gadgetin Channel (David Brandi) - Alwi Hanapi Harahap (International Journal of Cultural and Social Science, 2020)
This research highlights the rapid development of informationtechnology which has given rise to a modern, all-digital life traditionin a number of fields. The use of the internet in the global era as aform of advances in digital technology towards the vision ofmodernization of information is now growing drastically, especiallyin terms of meeting the needs of the information community in thesocio-economic field. Viewed from the business side, the use of theinternet for online media which is usually called social media, one ofwhich is YouTube. Youtube is very profitable for market players,investors, or industry players. In accordance with the formulation ofthe problem above, the purpose of this study is to find out "The roleof Youtube in building brand image communication on mobile phonereview content on the Gagdetin Channel by David Brendi". Theresearch method used is descriptive method, which is a method thatexplains the advantages and disadvantages of cellphone products, theobject of research at this time is based on the facts that appear in thevideo content as it is. This descriptive study only describes the role ofYoutube as a new medium, does not seek or explain relationships,does not test hypotheses or make predictions. The obstacle faced byDavid in building a technology brand image is that it is still difficultto find the audience's need for technology and tastes that are suitableto increase the brand image of an item.